Training MGMP German Teachers in Surabaya on AI-Assisted Cultural Poster Design - Audrey Gabriella Titaley; Wening Ruci; Kanya Catya; Silvy Adelia (Center for Community Service and Science and Technology Marketing - The Institute for Research and Community Service Universitas Negeri Surabaya, 2024)
This community service program aims to address the need for integrating local cultural elements into German language education for high school teachers in Surabaya and its surrounding areas. The focus of this initiative is to help German teachers incorporate East Javanese culture into their lessons using modern technology, particularly through AI-assisted poster design. The importance of this topic stems from the need to preserve local cultural heritage while enhancing language learning, fostering a deeper connection between students’ cultural identity and their foreign language education. The program was conducted in three stages: preparation, implementation, and evaluation. The preparation phase involved compiling accessible learning materials and ensuring all necessary resources were ready for the training sessions. The implementation phase provided hands-on workshops that introduced teachers to AI design tools such as Canva, Fotor, Piktochart, and ChatGPT, alongside instruction on poster design principles, including layout, typography, and bilingual content creation. In the evaluation phase, participants received feedback on their projects and refined their posters, integrating both German language elements and East Javanese cultural themes. The results demonstrated high participant engagement and successful skill development in using AI tools to create culturally relevant educational materials. Teachers produced bilingual cultural posters that effectively combined language instruction with local heritage promotion. This initiative not only enhanced teachers’ technological competencies but also strengthened their ability to integrate cultural content into their lessons, ensuring the preservation and appreciation of East Javanese culture in the context of German language education.